NBM-HD-1: A Novel Histone Deacetylase Inhibitor with Anticancer Activity. (20th October 2011) - Huang, Wei-Jan; Liang, Yu-Chih; Chuang, Shuang-En; Chi, Li-Ling; Lee, Chi-Yun; Lin, Chia-Wei; Chen, Ai-Ling; Huang, Jing-Shi; Chiu, Chun-Jung; Lee, Cheng-Feng; Huang, Chung-Yang; Chen, Chia-Nan
Abstract : HDAC inhibitors (HDACis) have been developed as promising anticancer agents in recent years. In this study, we synthesized and characterized a novel HDACi, termed NBM-HD-1. This agent was derived from the semisynthesis of propolin G, isolated from Taiwanese green propolis (TGP), and was shown to be a potent suppressor of tumor cell growth in human breast cancer cells (MCF-7 and MDA-MB-231) and rat glioma cells (C6), with an IC50 ranging from 8.5 to 10.3  μ M. Western blot demonstrated that levels of p21 (Waf1/Cip1), gelsolin, Ac-histone 4, and Ac-tubulin markedly increased after treatment of cancer cells with NBM-HD-1. After NBM-HD-1 treatment for 1–4 h, p-PTEN and p-AKT levels were markedly decreased. Furthermore, we also found the anticancer activities of NBM-HD-1 in regulating cell cycle regulators. Treatment with NBM-HD-1, p21 (Waf1/Cip1) gene expression had markedly increased while cyclin B1 and D1 gene expressions had markedly decreased. On the other hand, we found that NBM-HD-1 increased the expressions of tumor-suppressor gene p53 in a dose-dependent manner. Finally, we showed that NBM-HD-1 exhibited potent antitumor activity in a xenograft model. In conclusion, this study demonstrated that this compound, NBM-HD-1, is a novel and potent HDACi with anticancer activity in vitro and in vivo .